Ruby Bridges, winner of the 2016 Steinbeck Award (San Jose, California, 2023)
Ruby Bridges, winner of the 2016 Soul of the People award is also the only award recipient to appear in a Steinbeck work. In Travels with Charley, Steinbeck described the travails of a six-year-old black girl chosen to integrate an all-white elementary school in the Deep South of 1960. At the time, he did not know her name. Now, with the presentation of the Steinbeck Award to this civil rights icon on February 24, 2016, the names John Steinbeck and Ruby Bridges are now linked. Bridges called racism an adult disease and asked that we stop using children to spread it. John Steinbeck couldn't have said it better.